The Emergence of Post-Material Religious Politics: The Case of the Affinity Between Evangelicals and the Right-Wing in Democratic Chile (1995–2021) - Fediakova, E (Springer Science and Business Media Deutschland GmbH, 2024)
There has been a growing link between evangelical sectors and political life in Chile since the return to democracy. The inclusion of evangelicals in parties of the right-wing sector has been notorious and has enabled evangelicals to participate in elections, with some of them even winning public seats. This article explores the main aspects of this relationship in the 1995–2021 period in order to shed light on its origins and distinctive features, focusing on the development of this interaction since 2017. It is argued that the parallel processes of politicization and shift towards the right-wing of evangelical sectors occur within a post-material cleavage that was motivated by the search for new spaces to defend evangelical values in the political arena. © The Author(s), under exclusive licence to Springer Nature Switzerland AG 2024.